Influence of physical and water quality parameters on residual chlorine decay in water distribution network - Julius Caesar Kwio-Tamale; Charles Onyutha (Heliyon, 2024)
Chlorine is the most common disinfectant in drinking water distribution practice. World Health Organization recommends 0.2–5.0 mg/l of residual chlorine in drinking water. This paper analyzed influence of physical and water quality parameters on chlorine decay in drinking water distribution. Principal component analysis, directed tree and regression were used to investigate influence of these parameters on chlorine from water treatment plant to water consumption points. Results show that initial chlorine, electrical conductivity and distance explain 62 % of chlorine decay with estimated error of 0.045 mg/l. The decision-tree feature importance scores of initial chlorine and electrical conductivity were 0.47 and 0.23 respectively. The combined feature importance scores of physical parameters of distance (0.09), pipe diameter (0.06), flow velocity (0.03), pressure (0.02) and travel time (0.046) were less than that for initial chlorine concentration (0.47) alone. These results show that conventional chlorination at water treatment plants removes largely fast inorganic reactants leaving traces of slow organic reactants as the dominant secondary contaminants in water distribution system. The key policy recommendation is to use water quality parameters more than physical parameters in order to enable water utility managers maintain residual chlorine within safe public health standards.